Medical ontologies to support human disease research and control. (5th December 2005) - Hadzic, Maja; Chang, Elizabeth
In this paper, we discuss an ontology-based system and approach that provides interoperability support for research in and diagnosis of human disease. The proposed solution incorporates a prototype for a Generic Human Disease Ontology (GenDO) that contains common general information regarding human diseases. We adopted the DOGMA formalism for the description and terminology involving ontologies. The proposed GenDO presents the information in four 'dimensions': (a) disease types, (b) causes related to the disease, namely genetic causes (genes, gene complexes and candidate DNA sequence regions) and environmental causes (such as stress, family condition, childhood and age groups), (c) phenotype (observable characteristics of an organism) or symptoms, and (d) treatments available for the disease, such as drug therapy, chemotherapy and physiotherapy. The GenDO also aims to support the study of complex disorders caused simultaneously by many different factors, e.g., the case of psychiatric disorders. We illustrate how this GenDO helps to produce Specific Human Disease Ontologies (SpeDO) upon request, as a support tool for physicians and medical researchers.